Psychological and somatic symptoms among breast cancer patients in four European countries: A cross‐lagged panel model. (3rd September 2022) - Roziner, Ilan; Perry, Shlomit; Dahabre, Rawan; Bentley, Gabriella; Kelada, Lauren; Poikonen‐Saksela, Paula; Mazzocco, Ketti; Sousa, Berta; Karademas, Evangelos C.; Simos, Panagiotis; Pettini, Gretta; Oliveira‐Maia, Albino J.; et al.
Abstract: Psychological and physical health among women with breast cancer are linked. However, more research is needed to test the interrelations between psychological and somatic symptoms, over time and throughout the different phases of breast cancer treatment, to determine when and which interventions should be prioritized. Six hundred and eighty nine women from four countries (Finland, Israel, Italy and Portugal) completed questionnaires during their first clinical consultation following diagnosis with breast cancer, and again after 3 and 6 months. The questionnaires included self‐reported measures of psychological symptoms (Hospital Anxiety and Depression Scale; the Positive and Negative Affect Schedule Short Form) and somatic symptoms [selected items from the International European Organization for Research and Treatment of Cancer (EORTC) questionnaires]. Psychological and somatic symptoms were relatively stable across the three time‐points. Cross‐lagged paths leading from somatic to psychological symptoms (beta coefficients of 0.08–0.10), as well as vice‐versa (beta 0.11–0.12), were found to be significant. No evidence was found for cross‐cultural differences in mutual effects of psychological and somatic symptoms. The findings of this study call for tailoring personal interventions for breast cancer patients—either from a somatic perspective or a psychological perspective—and adjust them to the specific experiences of the individual patient.